Controllable Degradable Plasma Electrolytic Oxidation Coated Mg Alloy for Biomedical Application - Lu, Xiaopeng; Blawert, Carsten; Luthringer, Bérengère J.C.; Zheludkevich, Mikhail L. (Frontiers in Chemical Engineering, 2022)
A controllable degradable coating on Mg alloy based on plasma electrolytic oxidation (PEO) process is reported for the first time. The reported results show that introduction of silica nanoparticles into PEO electrolytes leads to their reactive incorporation in coatings and thus influencing the degradation behavior. Dissolution of amorphous phases facilitates chemical reaction with components of simulated body fluid, resulting in self-healing effect via redeposition of insoluble conversion products. The dynamic balance between dissolution of the original coating and reconstruction of corrosion layer is mainly determined by the phase composition of the coating as well as the surrounding corrosive medium.